Environmental filtering drives the establishment of the distinctive rhizosphere, bulk, and root nodule bacterial communities of Sophora davidii in hilly and gully regions of the Loess Plateau of China - Jing, Li; Jia-min, Ai; Xiao-dong, Liu; Ying-ying, Jiang; Chao-chao, Zheng; Rui-hua, Zhao; Zhen-shan, Deng (Frontiers in Microbiology, 2022)
The existence of non-rhizobial endophytes (NREs) in leguminous root nodules is a universal phenomenon, and they have the potential to enhance legume survival. However, the diversity and biogeographic patterns of microbial communities inhabiting root nodules are not well studied or understood. Here, we explored and characterized the diversity of NRE bacteria by using 16S rDNA gene high-throughput amplicon sequencing. Additionally, we compared the biogeography and co-occurrence patterns of the bacterial microbiota inhabiting the rhizosphere, the bulk soil and the root nodule bacterial communities associated with Sophora davidii, a native N-fixing wild leguminous shrub in hilly and gully regions of the Loess Plateau of China. The results showed the presence of a large diversity of bacteria belonging to 81 phyla, 154 classes, 333 orders, 463 families and 732 genera inside the nodules associated with Sophora davidii of indigenous legumes. Moreover, we found that the biogeographic patterns and assembly process of the rhizobia and non-rhizobia communities differed in the root nodule, the rhizosphere soil and the bulk soil. Furthermore, the microbial network diagram of co-occurrence patterns showed only specific microorganisms could colonize and thrive in the rhizosphere through the selection and filtering effects of roots. Overall, our results indicating that environmental filtering differed in the assembly of bacterial communities. Our study improves the understanding of the biogeographic patterns and diversity of bacterial microbiota inhabiting root nodules and can help quantify and define the root nodule assemblage process of Sophora davidii.